Westonci.ca is the best place to get answers to your questions, provided by a community of experienced and knowledgeable experts. Ask your questions and receive accurate answers from professionals with extensive experience in various fields on our platform. Experience the ease of finding precise answers to your questions from a knowledgeable community of experts.

The transverse axis of the hyperbola lies on the line y=-3 and has length 6, and the conjugate axis lies on the line x=2 and has length 8.

Sagot :

The general equation of a hyperbola is represented as: [tex]\mathbf{\frac{(x - h)^2}{a^2} - \frac{(y - k)^2}{b^2} = 1}[/tex]

The equation of the hyperbola is: [tex]\mathbf{\frac{(x - 2)^2}{9} - \frac{(y + 3)^2}{16} = 1}[/tex]

Recall that:

[tex]\mathbf{\frac{(x - h)^2}{a^2} - \frac{(y - k)^2}{b^2} = 1}[/tex]

The hyperbola lies on [tex]\mathbf{y = -3}[/tex]

This means that: [tex]\mathbf{k =y}[/tex]

So, we have:

[tex]\mathbf{k =-3}[/tex]

The length on the y-axis is 6.

So:

[tex]\mathbf{a = \frac 62}[/tex]

[tex]\mathbf{a = 3}[/tex]

Similarly, the hyperbola lies on [tex]\mathbf{x = 2}[/tex]

This means that: [tex]\mathbf{h =x}[/tex]

So, we have:

[tex]\mathbf{h =2}[/tex]

The length on the x-axis is 8.

So:

[tex]\mathbf{b = \frac 82}[/tex]

[tex]\mathbf{b = 4}[/tex]

At this point, we have:

[tex]\mathbf{k =-3}[/tex]

[tex]\mathbf{a = 3}[/tex]

[tex]\mathbf{h =2}[/tex]

[tex]\mathbf{b = 4}[/tex]

Substitute these values in [tex]\mathbf{\frac{(x - h)^2}{a^2} - \frac{(y - k)^2}{b^2} = 1}[/tex]

[tex]\mathbf{\frac{(x - 2)^2}{3^2} - \frac{(y -- 3)^2}{4^2} = 1}[/tex]

[tex]\mathbf{\frac{(x - 2)^2}{3^2} - \frac{(y + 3)^2}{4^2} = 1}[/tex]

Evaluate the exponents

[tex]\mathbf{\frac{(x - 2)^2}{9} - \frac{(y + 3)^2}{16} = 1}[/tex]

Hence, the equation of the hyperbola is: [tex]\mathbf{\frac{(x - 2)^2}{9} - \frac{(y + 3)^2}{16} = 1}[/tex]

Read more about equations of hyperbola at:

https://brainly.com/question/12919612